A Rare Case Diagnosed by Videothoracoscopic Lung Biopsy: Diffuse Pulmonary Meningotheliomatosis - Anton Dzian; Marek Malík; Ľuboš Hamada; Jozef Mičák; Ivana Gregorová; Gabriela Košturiaková (Case Reports in Pulmonology)
Diffuse pulmonary meningotheliomatosis (DPM) is reported as a diffuse parenchymal lung disease characterized by disseminating small asymptomatic nodules. These lesions are often detected incidentally as microscopic findings in lung specimens or autopsies examined by a pathologist. We report a case of a 60-year-old male asymptomatic patient presenting with multiple bilateral pulmonary nodules on high-resolution computed tomography and diagnosed by videothoracoscopic surgery. Differential diagnosis of patients presenting with diffuse indeterminate nodules is very important. Definitive diagnosis of DPM requires histopathology and most often videothoracoscopic lung biopsy.